Thickness dependent evolution of microstructure and magnetic properties of L10 (001) FePt films grown on TiN intermediate layer - Li, H.H. (2014)
2012 Digest APMRC - Asia-Pacific Magnetic Recording Conference: A Strong Tradition. An Exciting New Look!